1990
DOI: 10.1159/000247992
|View full text |Cite
|
Sign up to set email alerts
|

Transepidermal Potassium Ion, Chloride Ion, and Water Flux across Delipidized and Cellophane Tape-Stripped Skin

Abstract: The skin barrier was evaluated as a function of transepidermal water loss (TEWL) and electrolyte loss. Combination electrodes for chloride and pH determinations and a potassium ion electrode were utilized. Delipidization of the skin did not impair the electrolyte barrier, but did damage the epidermal water barrier. Cellophane tape stripping of normal stratum corneum resulted in an increase in outward transepidermal potassium and chloride ion flux, an increase in skin surface pH and an increase in TEWL. It appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…The average baseline (before stripping) and final (after stripping) TEWL values, along with their standard deviations, were 10.12 ± 2.65 g.m −2 h −1 and 61.48 ± 18.78 g.m −2 h −1 respectively. This increase in TEWL is due to the barrier disruption and is in agreement with previous work [13,14,16,27].…”
Section: Resultssupporting
confidence: 93%
“…The average baseline (before stripping) and final (after stripping) TEWL values, along with their standard deviations, were 10.12 ± 2.65 g.m −2 h −1 and 61.48 ± 18.78 g.m −2 h −1 respectively. This increase in TEWL is due to the barrier disruption and is in agreement with previous work [13,14,16,27].…”
Section: Resultssupporting
confidence: 93%
“…As occurs with calcium, it is likely that increased transepidermal water loss alters the epidermal potassium and phosphate concentration after barrier disruption due to increased passive loss. Studies by others have demonstrated increased potassium flux following disruption ofthe barrier (22). Calcium and potassium produce a synergistic inhibition ofbarrier recovery.…”
Section: Discussionmentioning
confidence: 98%
“…Disruption of the barrier is associated with increased ion flux across the skin (22 Additional evidence ofthe importance ofcalcium is shown by the effect ofinhibition ofcalcium transport on barrier recovery. Both verapamil and nifedipine, which are chemically unrelated and inhibit calcium transport into cells via the L channel (9), prevent the calcium induced inhibition of barrier repair.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many adaptations and modifications to the technique since its introduction. Examples include using rubbertipped scrapers in place of wood, using a variety of aspiration fluids, and adding a velvet imprinting pad (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Abrasion Techniquesmentioning
confidence: 99%